Evaluating the feasibility of an experimental paradigm for alcohol-involved sexual violence perpetration among active duty and veteran men - Amanda K. Gilmore; K. Nicole Mullican; Cecilia J. Moore; G. Mitchell Mazzone; Jessalynn R. Ellis; Ruschelle M. Leone; Kristen H. Walter; Rachel L. Tomko; Julianne C. Flanagan (European Journal of Psychotraumatology)
Background: Sexual assault is common in the military and heavy episodic drinking (HED) is a strong predictor of sexual violence perpetration.Objectives: The current study examined factors associated with engaging in alcohol-involved sexual violence perpetration (ASVP) in an experiment to extend ASVP research to military populations and against men.Method: We recruited 9 dyads (N = 18 men; active duty n = 12, veteran n = 6) over the age of 21 who reported HED together at least twice in the past month. Procedures were completed via video teleconference. Dyads completed a survey followed by a validated experiment assessing ASVP. Each participant had the opportunity to show either a sexual or neutral clip to an ostensibly intoxicated confederate in the military (gender randomly assigned at dyadic level) who reported a strong dislike of sexual content. Participants discussed their choices prior to making their decision. Discussions were transcribed and coded for verbalizations that supported (‘go cues’) or discouraged (‘stop cues’) their peer from engaging in ASVP during the experiment.Results: Results found that individuals with a perpetration history were less likely to engage in verbalizations of discouragement of peer ASVP (ß = −.563, p = .030), while participants were more likely to engage in verbalizations of discouragement of peer ASVP when the ostensibly intoxicated victim was a man (ß = .671, p = .025).Conclusions: This study laid the groundwork as a first step in understanding ASVP behaviour in a lab setting with military populations. Future research using fully powered samples can examine the role of peer influences on ASVP to harness for military sexual assault prevention.